The role of influenza viruses in the development of severe acute respiratory infection in patients admitted to Yekaterinburg hospitals during 2017–2018 epidemic season - Aleksandr V. Alimov; Svetlana S. Smirnova; Evgenia V. Lelenkova; Aleksandr Yu. Markaryan; Ivan V. Vyalykh; Vladislav K. Verevshchikov; Andrey B. Komissarov; Anna A. Sominina (Журнал микробиологии, эпидемиологии и иммунобиологии, 2020)
Objective. To study the role of influenza viruses in the development of severe acute respiratory infections (SARI) in patients admitted to Yekaterinburg hospitals during 2017-2018 epidemic season.Materials and Methods. A retrospective epidemiological analysis of influenza incidence in Yekaterinburg was conducted, 403 influenza and acute respiratory viral infections case sheets were studied, and PCR analysis of clinical samples from the patients for respiratory viral infections was performed.Results. During the epidemic period a total 27.0% of the Yekaterinburg population were reported with influenza and other SARI, with 1.8% patients hospitalized. 5.6% of the total number of patients admitted with influenza and SARI in Yekaterinburg hospitals were included in the study. The rate of the detection of influenza A and B viruses RNA in the clinical samples from the patients with SARI was 28.3%. The rates of the detection in PCR of influenza B/Yamagata, A(H1N1)pdm09 and A(H3N2) were 46.5, 20.2 and 10.5%, respectively.Conclusion. The study results indicated that influenza viruses remain significant pathogens of respiratory infections that required hospitalization. Among patients with SARI the highest incidence was observed in children of a younger age group and was mainly associated with influenza B virus of Yamagata lineage and influenza A virus (H1N1)pdm09. According to the results of a molecular genetic study, influenza A (H1N1) pdm09 viruses belonged to clade 6B.1, carried characteristic amino acid substitutions in hemagglutinin S84N, S162N (with the acquisition of a potential glycosylation site) and I216T and were similar to the A/Michigan/45/2015 vaccine strain. The influenza B viruses studied belonged to the Yamagata lineage, clade 3. The influenza B/Ekaterinburg /RII-4723S/2018 virus differed from the reference strain B/Phuket/3073/2013 by two amino acid substitutions in the hemagglutinin gene M251V and L172Q.